Performance Study of Biocoating Material with Damar and Silica Extract from Rice Husk on Mild Steel in NaOH Solution - Saputra, Radius Bambang; Nuryoto, N.; Pramudita, M. (ASEAN Journal for Science and Engineering in Materials, 2025)
Corrosion remains a critical challenge across various industries, necessitating the development of eco-friendly alternatives to conventional anti-corrosion methods. This study evaluates the performance of biocoating composed of rice husk silica and damar resin in inhibiting corrosion of mild steel in a 1M NaOH solution. The effects of drying temperature (27, 50, and 100°C) and duration (10, 30, 60 minutes) on corrosion resistance were systematically investigated. Optimal conditions were identified at 100°C for 10 minutes, achieving a corrosion rate of 0.041 mm/year and an inhibitor efficiency of 80%. Prolonged drying or higher temperatures resulted in reduced performance due to structural degradation. Comparative analysis revealed that these biocoating outperform untreated mild steel and are comparable to other natural inhibitors in terms of efficiency. The synergistic combination of rice husk silica and damar resin provides both physical and chemical protection, addressing the limitations of traditional methods. However, challenges in scaling up biocoating production, such as variability in material properties and integration into industrial processes, highlight the need for standardized protocols and further optimization. This study advances the understanding of biocoating mechanisms in alkaline environments, offering insights into their durability and effectiveness. The findings underscore the potential of rice husk silica and damar resin biocoating as sustainable, high-performance solutions for industrial corrosion protection.